Disaster Health Management Framework and the ASEAN Collective Measures for Rapid, Effective and Quality Operations of Emergency Medical Teams in The ASEAN Region - Kita, Taro; Ikeda, Shuichi; Chin , Abraham Zefong; Sanniasi , Thinagaraj; Aono , Mika (Universitas Gadjah Mada, 2025)
Introduction: The Project for Strengthening the ASEAN Regional Capacity on Disaster Health Management (ARCH Project) has contributed regional collaboration in disaster health management (DHM). Key achievements include the ASEAN Leaders’ Declaration on DHM (ALD DHM), and its Plan of Action (POA) (2019-2025). In 2019, the ASEAN Collective Measures (ACM) were initiated to support ASEAN Member States (AMS) in meeting the World Health Organization (WHO)’s Emergency Medical Teams minimum requirements (EMT-MR) and to strengthen coordination capacity for International EMTs (I-EMTs) operations. Objective: This study analyzes the progress and challenges in implementing the ACM work plan, and explores future strategies for sustainable DHM development in ASEAN. Methods: A qualitative review was conducted using reports and deliverables from ACM activities. The work plan included five areas: development of an AMS DHM database, confirmation of I-EMT receiving procedures, clarification of medical coordinator (MC) role, EMT item stockpile development, and joint EMT Operations. Results: A draft AMS DHM database was developed. Malaysia confirmed I-EMT receiving procedures and tested a joint EMT operation with Japan. Joint research on EMT items is ongoing. Conclusions: ACM serves as a regional problem-solving mechanism, supporting sustainable DHM through regional DHM activities and EMT operations